The Impact of Prophylactic Dexamethasone, Metoclopramide or both on Nausea and Vomiting After Laparoscopic Cholecystectomy - Ahmed N Thanoun (مجله كليه طب الكندي, 2020)
Background: Postoperative nausea and vomiting (PONV) are one of the most common complaints following laparoscopic cholecystectomy.